Shade in the Tropics: a phenomenological approach to man and his environment - Dawoud, Mohamed Abdo El-Raghy (The University of Edinburgh, 1984)
This thesis is concerned with the study of aspects of shade in the tropical urban environment. It attempts to reveal the primacy of the qualitative nature of this phenomenon and puts its quantitative description in its proper place.

A phenomenological analysis of the meanings and values of shade leads to the qualitative choice of the courtyard as a viable and relevant form [both socioculturally and climatically] upon which a systematic quantitative investigation of shade is carried out by developing a mathematical model which represents the interaction taking place between solar shading and groups of courtyard forms. Taking the city of Abu Dhabi as a typical example of the prevailing climatic conditions in the Gulf, the model is implemented on a computer and utilized to generate detailed data of the time -averaged distribution of shade on the ground.

This quantitative investigation identifies the ranges and the effects of the geometrical parameters of courtyards on the time -averaged distribution of shading and defines their inter -relationships. The generative potentials of the model are illustrated through the interplay between research and design.